Customer experience and satisfaction with Suzuki motorbikes in comparison to premium Indian and Chinese Motorcycle brands. - Ahmed, Iftekhar (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.